Analisis Perbedaan Model Pembelajaran Problem Based Learning dan Discovery Learning pada Latihan Soal Matematika Menggunakan Uji Anova Satu Arah - Ade Andriani; Delviananda Harahap; Tricinta Yospin Wina Harianja; Widya Riatama Pandiangan; Winda Hutahaean (Journal on Education, 2024)
This study aims to analyze the difference in effectiveness between the Problem Based Learning (PBL) and Discovery Learning (DL) models on the mathematics practice test scores of 8th-grade students at SMP N 11 Medan during the 2024/2025 academic year. The research employs a quantitative method with a quasi-experimental design. The subjects consist of two groups of students, with each group using one of the learning models. The data collected, in the form of mathematics practice test scores, were analyzed using one-way ANOVA to determine the differences in average learning outcomes between the two groups.The results show that, based on both manual calculations and SPSS software analysis, the calculated was 0.11, with the critical being at a 5% significance level. Since and the significance value was (), the null hypothesis was accepted, indicating no significant difference in the mathematics practice test scores of students taught using the PBL and DL models. The normality and homogeneity of variance tests also confirmed that the data met the assumptions of normality and homogeneity.Based on these findings, it can be concluded that both PBL and DL learning models have comparable effectiveness in improving students' learning outcomes on mathematics practice tests. The choice between these models can be made based on the needs and characteristics of the students, without concern for significant differences in learning outcomes. Other factors, such as student characteristics, the quality of instructional implementation, and the content being taught, may influence the study's results.